2022
DOI: 10.3389/fvets.2022.830275
|View full text |Cite
|
Sign up to set email alerts
|

Focused Cardiac Ultrasound to Detect Pre-capillary Pulmonary Hypertension

Abstract: BackgroundEarly recognition of pre-capillary (PC) pulmonary hypertension (PH) benefits dogs, allowing earlier treatment and improving prognosis. The value of focused cardiac ultrasound (FCU) to diagnose PH and assess its severity has not been investigated yet.HypothesisA subjective 10-point FCU pulmonary hypertension score (PHS) allows diagnosis and assessment of severity of PCPH.AnimalsThis study involved fifty client-owned dogs.MethodsDogs, recruited between September 2017 and February 2020, were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 30 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Pulmonary hypertension was one of the lowest‐scoring cardiovascular pathologies. One study demonstrated that POCUS was not sensitive in screening for pulmonary hypertension, 31 whereas another found that, with a more complete protocol and training, diagnosis of pulmonary hypertension was improved 32 . It follows that most respondents to our survey lack confidence in using POCUS for diagnosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Pulmonary hypertension was one of the lowest‐scoring cardiovascular pathologies. One study demonstrated that POCUS was not sensitive in screening for pulmonary hypertension, 31 whereas another found that, with a more complete protocol and training, diagnosis of pulmonary hypertension was improved 32 . It follows that most respondents to our survey lack confidence in using POCUS for diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…One study demonstrated that POCUS was not sensitive in screening for pulmonary hypertension, 31 whereas another found that, with a more complete protocol and training, diagnosis of pulmonary hypertension was improved. 32 It follows that most respondents to our survey lack confidence in using POCUS for diagnosis. No standardised protocol for CV-POCUS has been described, and assessments remain subjective.…”
Section: Discussionmentioning
confidence: 95%
“…1 Right heart changes secondary to PH include right ventricular hypertrophy, PA/trunk enlargement, right ventricular or atrial enlargement, flattening of the interventricular septum, and prominent papillary muscles. 1,3,6,[11][12][13][14] Signs of a congestive state have also been evaluated in patients with PH including CVC distention, gallbladder edema, hepatic vein distention, and peritoneal effusion. 1,3,11,12,15 A previous study reported that an echocardiographic 10-point pulmonary hypertension score (PHS), based on these anatomical changes, accurately identified patients with moderate to severe PCPH.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,6,[11][12][13][14] Signs of a congestive state have also been evaluated in patients with PH including CVC distention, gallbladder edema, hepatic vein distention, and peritoneal effusion. 1,3,11,12,15 A previous study reported that an echocardiographic 10-point pulmonary hypertension score (PHS), based on these anatomical changes, accurately identified patients with moderate to severe PCPH. 11 Patients with PH are often presenting on an emergent basis and have a worse prognosis than patients without PH (in both people and animals).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation